Financial Performance Assessment of Flat Buildings Using Life Cycle Cost and Cost–Benefit Analysis - Griselda Junianda Velantika; Reguel Mikhail; Karina Meilawati Eka Putri; Elok Dewi Widowati; Rizqi Alghiffary; Muhamad Fauzan Akbari (Advance Sustainable Science Engineering and Technology, 2025)
Buildings resulting from construction projects are durable assets and decisions related to construction projects have enduring impacts. In many cases, building owners prioritize only the initial costs, such as building design, construction, and equipment costs, while neglecting the future operation and maintenance costs. This research studies life cycle costing (LCC) analysis to evaluate the financial feasibility of urban housing. The LCC calculates all the costs incurred and benefits during the building's operation. The cost is generated from construction, operational, and maintenance costs. At the same time, the benefit breaks down into flat rental costs, retail rental costs, and parking costs. The costs incurred are estimated over 25 years, and the parameters of feasibility are net Present Value (NPV), Benefit-Cost Ratio (BCR), and Internal Rate of Return (IRR). The study generates negative NPV, BCR < 1, and 0.61% of IRR. It indicates that the project is not feasible. This research gives alternatives to make the project feasible. This study employed a trial-and-error approach to ascertain the viability of investing in flat rentals by systematically adjusting rental rates. Incremental adjustments to rental rates are tested by a series of rate hikes of 50%, 100%, 150%, and 200% using a trial-and-error approach. The project will become feasible if the flat rate increases to 150-200% of the initial rental rate.